Training on Building Multiple Choice Exam Question Applications with Php+Ajax+Mysql - Nasution, Adnan Buyung; Hrp, Ahir Yugo Nugroho; Yudi, Yudi; Fauzi, Muhammad; Sari, Ria Eka; Gunawan, Heri (Jurnal Pengabdian Masyarakat Bestari, 2025)
This training aims to provide participants with the knowledge and skills to develop web-based exam question applications using PHP and AJAX technologies. The activity is designed to enhance participants' capacity in developing dynamic and responsive applications that can be utilized in various educational institutions. The training involves theoretical sessions and hands-on practice, allowing participants to understand basic concepts and implement simple exam question applications with features such as question creation, answer management, and automatic grading.